Upheaval buckling of pipelines triggered by the internal pressure resulting from the transportation of oil and gas: theoretical discussions and geometrically nonlinear analysis using Finite Element Method. - Craveiro, Marina Vendl (2017)
The pipelines used to transport oil and gas from the wellheads to the distribution and refining sites can be subjected to high levels of pressure and temperature. Under such conditions, the pipelines tend to expand, but, if the expansion is inhibited, a significant compressive axial force can arise, leading to their buckling, which can occur in the horizontal or vertical plane. In this context, the objective of the present work is to analyze the upheaval buckling of pipelines, considering the internal pressure to which they are subjected during the transportation of oil and gas as its only triggering. Using the concept of effective axial force, it aims at discussing two different approaches for considering the internal pressure in buckling problems: distributed loads dependent on pipeline curvature and equivalent compressive axial forces with follower and non-follower characteristics. It also discusses the influence of using static or dynamic analysis for such approaches. Concerning the upheaval buckling itself, the work intends to analyze and compare the influence of the soil imperfection amplitudes to the influence of the friction between the pipeline and the ground in the critical loads and in the post-buckling configurations of the pipeline. Besides theoretical research, the objectives are achieved through the development of various numerical models, since geometrically-simple models, without the consideration of the interaction between the pipeline and the ground, until more complex models, with the use of contact models to detect the ground and its imperfections. The models are developed in Giraffe (Generic Interface Readily Accessible for Finite Elements) using geometrically-exact finite element models of beams, undergoing large displacements and finite rotations. Through the research, it is concluded that there is an equivalence between the application of the internal pressure as a distributed load dependent on pipeline curvature and the application of the internal pressure as a follower compressive axial force. Besides this, it is demonstrated that the type of the analysis (static or dynamic) depends on the nature of the physical system analyzed. With the aid of results presented in terms of internal pressure, classical results about the influence of the imperfection amplitudes and of the friction between the pipeline and the ground in buckling are confirmed. It is also showed that the imperfection amplitudes analyzed play a more important role in the post-buckling configurations of the pipeline than the friction.